2012
DOI: 10.1111/j.1538-7836.2012.04745.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen counteracts the antiadhesive effect of fibrin‐bound plasminogen by preventing its activation by adherent U937 monocytic cells

Abstract: Summary Background Fibrinogen and plasminogen strongly reduce adhesion of leukocytes and platelets to fibrin clots, highlighting a possible role for these plasma proteins in surface-mediated control of thrombus growth and stability. In particular, adsorption of fibrinogen on fibrin clots renders their surfaces non-adhesive, while the conversion of surface-bound plasminogen to plasmin by transiently adherent blood cells results in degradation of a superficial fibrin layer, leading to cell detachment. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
(55 reference statements)
1
5
1
Order By: Relevance
“…Therefore, the conclusions and models generated in our previous studies of fibrinogen deposition on hard surfaces such as mica or glass [28,29] should provide guidance for future analyses. Likewise, our present studies and previous low resolution demonstration that fibrinogen accumulates in a thin superficial layer of fibrin clots [27] may guide future analyses of spatial distribution of fibrinogen and other proteins on the flow surface of thrombi in vivo .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Therefore, the conclusions and models generated in our previous studies of fibrinogen deposition on hard surfaces such as mica or glass [28,29] should provide guidance for future analyses. Likewise, our present studies and previous low resolution demonstration that fibrinogen accumulates in a thin superficial layer of fibrin clots [27] may guide future analyses of spatial distribution of fibrinogen and other proteins on the flow surface of thrombi in vivo .…”
Section: Discussionsupporting
confidence: 65%
“…The underlying mechanism of this process involves the adsorption of intact fibrinogen in a thin superficial layer of fibrin clots [27] and its self-assembly leading to the formation of a nanoscale (~10 nm) multilayer matrix [28,29]. The fibrinogen matrix is extensible, which makes it incapable of transducing strong mechanical forces via cellular integrins, resulting in weak intracellular signaling and infirm cell adhesion [16,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…We therefore anticipated that fibrinogen might disturb cell functions that are considered instrumental in stress resistance and tubular repair. Antiadhesive effects of fibrinogen have previously been described in other cell types and have mainly been interpreted as a mechanism to limit uncontrolled thrombus growth (23,24). In vivo, we could not find any significant changes in adhesion-dependent injury and repair processes such as tubular cell detachment or epithelial repopulation of denuded basement membranes.…”
Section: Discussioncontrasting
confidence: 39%
“…We and other groups have shown that pure fibrin, which is a highly adhesive substrate for platelets and leukocytes, loses its capacity to support cell adhesion in the presence of soluble fibrinogen or after coating of fibrin clots with fibrinogen (19,22,45). The mechanism by which fibrinogen neutralizes the adhesion-promoting capacity of fibrin is evidently the deposition of the nonadhesive fibrinogen multilayer on its surface.…”
Section: Discussionmentioning
confidence: 99%